Developing Of Cognitive Assessment Instrumens Of High Order Thinking Skills In Small Ball Game Material - Hadinata, Reza; Adrizal, Mohd.; Daya, Wawan Junresti; Mardian, Roli; Ilham, Muhammad; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
The Instrument of Higher Level Thinking Skills in Small Ball Games is an assessment instrument in sports subjects, especially in the sports of tennis, table tennis and badminton. This instrument is used to measure students' Higher Level Thinking abilities. This study aimed to: (1) produce a test instrumen that is feasible and meets the requirements for use in measuring the Higher Order Thinking Skills of students majoring in Sports Education, and (2) find out the characteristics of the instrumen of Higher Order Thinking Skills on Small Ball Game material of students majoring in Sports Education.This study used a modification development model from Wilson, Orindo, and Antonio, consisting of three stage: (1) designing the tests, (2) conducting test trials, and (3) taking test measurements. The population in this study was 308 students. The sampling technique was carried out using a total sampling technique. The trial subjects in this study consisted of 152 students, while measurement subject consisted of 156 students. Test instrument products were assessed by experts through a content validation sheet, where there are 2 experts, namely measurement experts (test construction experts) and sports education experts (material experts). Analysis was carried out using Item Response Theory with the help of the QUEST program. The results of the analysis in this study indicate that the test instrumen is feasible and meets the requirements for use in measurements. The conclusions in this research are a) The test instrument has been proven to be valid by experts; b) The test instrument has questions that are in the good category based on the results of the unidimensional test analysis; c) The test instrument is in the high category based on the information function.